ATTENTION TO PEOPLE - THE YEAR OF QUALITY EDUCATION - OPENED A WIDE WAY FOR THE PROTECTION OF HUMAN RIGHTS AND INTERESTS AND THE DEVELOPMENT OF EDUCATIONAL REFORMS (Conferencea, 2023)
In this article, the implementation of the state program for the implementation of the development strategy of New Uzbekistan for 2022-2026 in the "year of attention to people and quality education" by the Decree of the President of 2023 and how the reforms provided for in it are implemented in the life of society Information is given that it is gaining importance.